2022
DOI: 10.1371/journal.pone.0274179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a synbiotic as an antibiotic alternative on behavior, production performance, cecal microbial ecology, and jejunal histomorphology of broiler chickens under heat stress

Abstract: The aim of this study was to examine if synbiotics present similar efficiency to a common antibiotic used in poultry production under heat stress (HS) conditions. Two hundred and forty-one-day-old male Ross 708 broiler chicks were distributed among 3 treatments with 8 pens per treatment of 80 birds each for a 42-day trial. From day 15, birds were heat stressed (32°C for 9 h daily, HS) and fed the basal diet (CONT), the basal diet mixed with an antibiotic (Bactiracin Methylene Disalicylate) (0.05 g/kg of feed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…This enhancement could directly correlate with the beneficial impact on the gut bacterial community by establishing population balance and averting digestive infections that could harm the intestinal tissue. These outcomes were in concurrence with those of Taklimi et al (2012) , Hassanpoura et al (2013) , Jiang et al (2020) and Mohammed et al (2022) .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This enhancement could directly correlate with the beneficial impact on the gut bacterial community by establishing population balance and averting digestive infections that could harm the intestinal tissue. These outcomes were in concurrence with those of Taklimi et al (2012) , Hassanpoura et al (2013) , Jiang et al (2020) and Mohammed et al (2022) .…”
Section: Discussionsupporting
confidence: 71%
“…Several studies have demonstrated the potential benefits of using synbiotics instead of antibiotics in commercial broiler chickens ( Mohammed et al, 2022 ; Salem et al, 2023 ). Prebiotics, consisting of non-digestible oligosaccharides, can regulate or alter microbes’ makeup and/or function, helping preserve a healthy microbiota that inhibits the growth of pathogens via various regulatory mechanisms ( Ballini et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a study, researchers observed that the synbiotic (50 ppm of PoultryStar me US ) increased the antioxidant ability and thus lead to better poultry meat quality ( Hu et al, 2022 ). In another study, the same research team showed that use of the synbiotic led to better growth, behavior and jejunal histomorphology in broilers specifically in heat stress ( Mohammed et al, 2022 ).…”
Section: The Best Alternative For Improving Growth and Product Qualitymentioning
confidence: 99%